2014
DOI: 10.1021/ic500919e
|View full text |Cite
|
Sign up to set email alerts
|

Potassium–Sulfur Batteries: A New Member of Room-Temperature Rechargeable Metal–Sulfur Batteries

Abstract: We report room-temperature rechargeable potassium-sulfur (K-S) batteries using ordered mesoporous carbon (CMK-3)/sulfur and polyanilime (PANI) coated CMK-3/sulfur composites as the cathode and metallic potassium as the anode. The electrochemical reaction mechanism was investigated by electrochemical tests, TEM, XRD, and Raman spectra. It was found that K-S batteries delivered two reduction peaks located at about 2.1 and 1.8 V and one oxidation peak at about 2.2 V, respectively. Meanwhile, K2S3 was the major di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
228
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 173 publications
(236 citation statements)
references
References 56 publications
7
228
1
Order By: Relevance
“…Potassium–sulfur batteries (KSBs) have also been explored; one example uses ordered mesoporous carbon (CMK‐3)/sulfur and polyanilime (PANI) coated CMK‐3/sulfur composites as the positive electrode and K‐metal as the negative electrode with 1.0 m KClO 4 in tetraethylene glycol dimethyl ether (TEGDME) cycled between 1.2–2.4 V at 50 mA g −1 . CMK‐3/sulfur composites contained 40.8 wt% S and produced initial discharge and charge capacities of 512.7 and 522.5 mA h g −1 , respectively (see Figure 14 ).…”
Section: Full Cell Construction and Other K‐based Batteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Potassium–sulfur batteries (KSBs) have also been explored; one example uses ordered mesoporous carbon (CMK‐3)/sulfur and polyanilime (PANI) coated CMK‐3/sulfur composites as the positive electrode and K‐metal as the negative electrode with 1.0 m KClO 4 in tetraethylene glycol dimethyl ether (TEGDME) cycled between 1.2–2.4 V at 50 mA g −1 . CMK‐3/sulfur composites contained 40.8 wt% S and produced initial discharge and charge capacities of 512.7 and 522.5 mA h g −1 , respectively (see Figure 14 ).…”
Section: Full Cell Construction and Other K‐based Batteriesmentioning
confidence: 99%
“…a) Reactions in the KSBs, b) schematic of electrode reactions in the composite electrodes, and c) charge–discharge profiles at 50 mA g −1 . Adapted with permission . Copyright 2014, American Chemical Society.…”
Section: Full Cell Construction and Other K‐based Batteriesmentioning
confidence: 99%
“…Nevertheless, pure potassium anodesa re reported in the literatures for use in room-temperature potassium batteries, [17,[30][31][32] potassium-O 2 batteries, [33] and potassium-sulfur batteries. [30,34,35] It is relatively difficult to passivate ap otassium-metal anode during long-term running. Wu et al found that KFSI/diglyme electrolyte could realize highly stable potassium deposition/stripping at room temperature ( Figure 4).…”
Section: Potassiummentioning
confidence: 99%
“…[9] Sulfur can facilitate a 2-electron charge transfer and theoretically deliver a high gravimetric capacity of 1672 mA h g −1 . In addition to the primary emphasis on lithium-sulfur (Li-S) batteries, [10] sodiumsulfur batteries, [11] magnesium-sulfur (Mg-S) batteries, [12] potassium-sulfur batteries, [13] and aluminum-sulfur (Al-S) batteries [14] have also received significant attention. However, to date, there has been only one study on calcium-sulfur (Ca-S) batteries, and the Ca-S cells demonstrated in that study were not reversible.…”
mentioning
confidence: 99%